Weaving the Roadmap Tradition in Scope and Methodology: Preparation of a Strategic Plan for Contemporary Islamic Education - Nabila, Jihan Zulfa; Mufidah, Zahrotul; Syahariya, Aura Anya; Muttaqin, M. Imamul; Rahimah, Tin (Proceeding of International Conference on Islamic Education (ICIED); Vol 10 No 1 (2025): Proceeding of International Conference on Islamic Education (ICIED), 2025)
This study, entitled "Arranging the Roadmap Tradition in Scope and Methodology: Compiling a Contemporary Islamic Education Strategic Plan," was conducted at Ma'had Aly UIN Maulana Malik Ibrahim Malang. This study departs from the need to reformulate Islamic education strategies so that they remain rooted in classical scientific traditions, yet adaptive to changing times. Using a qualitative approach and in-depth interview methods, this study explores the views of Ma'had managers and students regarding the process of integrating turats values in the preparation of the institution's strategic plan. The results show that the Ma'had Aly roadmap functions not only as a planning instrument but also as a dialectical space between tradition and modernity. The synthesis of the two gives birth to a strategic direction for Islamic education that is contextual, reflective, and characterized by Islamic boarding school scholarship.